RANCANGAN SISTEM INFORMASI RIWAYAT PERBAIKAN RECEIVER BERBASIS WEB PADA PT MNC VISION - Jenie Sundari; Abdul Azis (Jurnal Informatika, 2019)
PT. MNC VISION is a company engaged in satellite tv. Problems in dealing with this company is, not the existence of the sikronisasi history of the condition of the receiver. Where the receiver is used as a means of capturing a signal for satellite tv. This receiver at pinjamkan party company to the customers. Logging with the manual for this receiver, so that in the event of damage or repairs on the receiver, the receiver does not condition history quickly note the results. This author makes issue of architecture history information system improvements to receivers using the method waterfall. With this method, the author analyzes the system requirements, designing the look of the web, designing the application and test the success of the system. The result is, in the form of web-based information system where data damage receiver can be directly input and known problems of the damage, expected to speed up the report the condition of the receiver, allowing parties to repair damage in handling receiver.  Keywords :  inventory, web, receiver, waterfall